The importance of multidisciplinary approach in management of pressure injury in elderly with multiple comorbidities - Kusumawardhani, Dina; Yusharyahya, Shannaz Nadia; Legiawati, Lili; Astriningrum, Rinadewi; Adistri, Kara (Journal of General - Procedural Dermatology and Venereology Indonesia, 2023)
Background: Pressure injury (PI) can occur as a result of prolonged bed rest in immobilized patients. The healing process is often slow if the wounds are not managed comprehensively, particularly in elderly patients or patients with neurological disorder, diabetes mellitus, and malnutrition. Proper treatment can improve the healing process. Case illustration: A 66-year-old female with multiple comorbidities presented with PI on the left lower back, as well as the sacral and right gluteal regions. She was diagnosed with grade 3 and unstageable PI, and was treated using a multidisciplinary approach. Her wounds were treated with a combination of hydrogels and polyurethane foam dressings. Discussion: Managing comorbidities, optimizing local wound care, regular repositioning in special mattress, and improving nutritional status are necessary to accelerate healing in cases of PI. There was an increase in the wound granulation and epithelialization, as well as a decrease in the ulcer size and exudates after 16 weeks of treatment. A considerable amount of time is needed to treat grade 3 and unstageable PI in an immobile elderly patient with multiple comorbidities. Conclusion: Multidisciplinary collaboration among healthcare workers is essential for the treatment of PI in elderly populations.